Exploring the regenerative potential for community-based ecotourism in the Niah National Park in Sarawak, Malaysia - Qi, Fenjie; Pforr, Christof; Justin Dit, Terry (Taylor & Francis, 2024)
Regenerative tourism has recently gained much attention, joining other regenerative ideas like regenerative agriculture, regenerative design, and regenerative development. It promotes value-driven approaches that prioritise community-based tourism development and aims to enhance local well-being by fostering alternative pathways. Concerns regarding the future of the tourism sector as well as its contribution to community empowerment have increased in response to the Covid-19 pandemic, particularly in the case of tourism-dependent and developing economies. In the context of the Niah National Park in Sarawak, Malaysia, this research note critically reflects on past and current development approaches and discusses regenerative tourism potentials.